DIALEKTIKA COSPLAY, ESTETIKA, DAN KEBUDAYAAN DI INDONESIA - Deni Setiawan (Institut Seni Indonesia Yogyakarta, 2013)
Culture and the type of clothing cosplay, sustainably develop in some parts of theworld, such as in the United States, Japan, Australia, Paris, London, Italy, and not least inIndonesia. As well as the animation concept inherent in Japanese culture, cosplay clothingbervisual be, of course, has its advantages and disadvantages, as well as shifting ideas whendiadobsi by a particular country. It is inevitable, characteristics and character animation as areference cosplay clothing manufacture, changing its form, concept, and material when appliedin Indonesia. Cosplay Indonesia, for example, how this all adopt dialihmaterialkan business, aswell as experienced changes in search of ideas to show all the elements of Indonesia 's. Makingthe next cosplay outfit based on stories, fairy tales, novels, legends, and comics in Indonesia.This arrangement is not without reason and without creativity, but more depth can bediscussed as a form of acculturation between the ideas of Japanese and Indonesian culture,which is packed into a cosplay outfit. On the other arts areas, the concept of cosplay is oftenshown as a costume show. For example, in the theater, revue, or a play-play in an event thatfeatured performances on the stage space . The concept of clothing with a special place andtime, is a simple concept of cosplay. Visualize concepts ideas or writings on clothing image andmakeup, which is transformed into three- dimensional shapes. Cosplay should be viewed as adiscourse of culture and art, by adopting textual ideas, concepts imagination image, into formssuch a unique and beautiful. Key words : cosplay, cosplayer, aesthetic principles, various forms, and ideology. Budaya dan jenis pakaian cosplay, secara berkesinambungan berkembang di beberapabelahan dunia, seperti di Amerika Serikat, Jepang, Australia, Paris, London, Italia, dan tidakterkecuali di Indonesia. Seperti halnya dalam konsep animasi yang melekat pada budayaJepang, bervisual menjadi pakaian cosplay, tentunya memiliki kelebihan dan kekurangan, sertamengalami pergeseran ide-ide manakala diadobsi oleh negara tertentu. Tidak dapat dipungkiri,ciri khas dan karakter animasi sebagai rujukan pembuatan pakaian cosplay, mengalami perubahan bentuk, konsep, dan material ketika diaplikasikan di Indonesia. Cosplay Indonesiamisalnya, bagaimana usaha adobsi ini dialihmaterialkan, serta mengalami perubahanperubahandalam pencarian ide-ide dengan menampilkan unsur-unsur ke-Indonesia-an.Pembuatan pakaian cosplay pada selanjutnya berdasarkan pada cerita, dongeng, novel,legenda, dan komik-komik di Indonesia. Penggubahan ini bukan tanpa alasan dan tanpakreativitas, tetapi lebih mendalam dapat dibahas sebagai bentuk akulturasi antara ide-idekebudayaan Jepang dan Indonesia, yang dikemas menjadi pakaian cosplay. Pada wilayahkesenian lain, konsep cosplay juga sering ditampilkan sebagai sebuah kostum pertunjukan.Misalnya pada pertunjukan teater, pertunjukan tari-tarian, atau sebuah lakon-lakon yangditampilkan dalam sebuah acara pertunjukan diatas ruang pentas. Konsep pakaian dengantempat dan waktu khusus, adalah konsep sederhana dari cosplay. Konsep-konsep yangmemvisualkan ide-ide gambar ataupun tulisan tentang pakaian dan tata rias, yangditransformasikan menjadi bentuk tiga dimensi. Cosplay seharusnya dipandang sebagaiwacana kebudayaan dan kesenian, dengan mengadobsi ide-ide tekstual, konsep imajinasigambar, menjadi bentuk-bentuk rupa yang unik dan indah. Kata-kata kunci: cosplay, cosplayer, prinsip estetika, ragam bentuk, dan ideologi.